Cozen's phenomenon: a remindera. Issue 3 (August 2013) - Dorman, S; Jariwala, A; Campbell, D
A four-year-old child attended Accident and Emergency following a fall from a slide with a displaced and angulated proximal tibial metaphyseal fracture. Treatment included closed manipulation under anaesthesia and an above knee cast for seven weeks. Serial radiographs over the following few months were satisfactory demonstrating good alignment and evidence of healing. However, at four-months review new-onset genu valgum with mechanical axis deviation was noted. No evidence of spontaneous resolution was noted over the following 12 months and hence a corrective hemi-epiphysiodesis was performed. At 12-months post-operatively, there was marked clinical and radiographical improvement in alignment. Classically Cozen's phenomenon is described as the late-onset post-traumatic valgus deformity associated with proximal tibial metaphyseal fractures in children. We want to reemphasise the early recognition of children at risk of this unique complication. In addition, we wish to highlight the progression of the late-onset valgus and its subsequent management.